Field response of wheat genotypes to spot blotch under different sowing dates at Rampur, Chitwan, Nepal - Nepal, S.; Shrestha, S. M.; Manadhar, H. K.; Yadav, R. K. (Journal of Agriculture and Forestry University, 2020)
Wheat spot blotch, caused by Bipolaris sorokiniana (Sacc.) Shoemaker has emerged as an important fungal disease for its economic losses in Nepalese wheat production system due state of poor resistance to spot blotch exacerbated by terminal heat stress in popular released wheat varieties. Thus it has engendered a dire need for identification of new robust and improved varieties with spot blotch resistance, suited to different sowing conditions. A field experiment was conducted at premises of Agriculture and Forestry University, Rampur to elucidate the field response of twenty wheat genotypes under different sowing conditions (early- 25th November, normal- 10th December, and late- 25th December) to spot blotch by using Split plot design, each treatment with three replicates, during 2017-2018. The analysis of variance revealed highly significant interaction (p